Magyar Kir. Csendőrség és az országgyarapítások : 1939-1941 - Suba, János (Közép-Európai Közlemények, 2016)
The Grendarmerie took part in the occupation of the returned territories. They secured military police services to the entering military forces, and carried out public safety tasks in the occupied areas. These were completed in accordance with the pace of territory occupation, using forces with different size and structure according to the particular task. The forces were delegated from all over the country, leaving their original duties behind; for example, for the occupation of Northern Hungary and later Subcarpathia one thousand gendarmes were separated each. Parallel to this, police forces were being structured in the returned territories, which modified the position of the grendarmerie significantly. Also, new organizational units were established and the intention was to keep the 1913’s structure rationally. After 1941 there were not major organizational changes in the areas any more. The operation of the body included the establishment of new security forces and grendarmerie companies, increasing the number of specialized subunits, quality improvement and finally wartime tasks.